Downplaying Trauma and Tragic Backstories with Sarcasm: A Critical Discourse Analysis of Freeze Your Brain Lyrics - Jasmine Kayla Az-Zahra (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
This study explores how trauma and tragic backstories are downplayed by the use of sarcasm through analysis of the lyrics of Freeze Your Brain, written by Laurence O’Keefe and Kevin Murphy and performed by Ryan McCartan in the Heathers: The Musical Original Broadway Cast recording that was uploaded on June 10th, 2014, a dark comedy that critiques high school hierarchies. Using Norman Fairclough’s Critical Discourse Analysis (CDA) model as the primary framework, this study analyzes how lexical choices, grammatical structures, and social contexts turn traumatic personal experiences into enjoyable humor and irony for both characters and audiences. The critical discourse analysis reveals that sarcasm in the musical number not only masks emotional vulnerability but also frames psychological numbness as an aspirational state of control, emotional regulation, and perceived maturity. Further, the linguistic transformation in the lyrics serves as a defense mechanism for the character and shapes listener interpretations of coping and resilience in the face of adversity. The findings contribute to broader discussions on emotional suppression, consumer-based escapism, performative detachment, and ideological messaging in musical theatre texts.